2008
DOI: 10.3748/wjg.14.2308
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CXCR4 activity with AMD3100 decreases invasion of human colorectal cancer cells in vitro

Abstract: Inhibition of CXCR4 activity with AMD3100 decreases invasion of human colorectal cancer cells in vitro. World J Gastroenterol 2008; 14(15): 2308-2313 Available from: URL: http://www.wjgnet. com/1007-9327/14/2308.asp DOI: http://dx.doi.org/10.3748/ wjg.14.2308 INTRODUCTIONStromal cell-derived factor-1 (SDF-1 or CXCL12) and its unique receptor CXC chemokine receptor-4 (CXCR4) have prominent roles in invasion and metastasis of a diverse number of cancers. The interaction between SDF-1 and CXCR4 has been shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 28 publications
5
50
0
Order By: Relevance
“…The proliferation rate and growth patterns of tumors have significant impacts on disease development and prognosis of the patients; indeed, the proliferation rate of tumor cells can indirectly reflect the tumor malignancy (Ravi et al, 1998). Proliferation of malignant cells can be affected by changes in many different proteins, but evidence indicates that the CXCL12-CXCR4 biological axis is important to this process (Chen et al, 2006;Li et al, 2008). We found that, in fact, the proliferation rate of pancreatic cancer cells was significantly increased in the presence of exogenous CXCL12.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation rate and growth patterns of tumors have significant impacts on disease development and prognosis of the patients; indeed, the proliferation rate of tumor cells can indirectly reflect the tumor malignancy (Ravi et al, 1998). Proliferation of malignant cells can be affected by changes in many different proteins, but evidence indicates that the CXCL12-CXCR4 biological axis is important to this process (Chen et al, 2006;Li et al, 2008). We found that, in fact, the proliferation rate of pancreatic cancer cells was significantly increased in the presence of exogenous CXCL12.…”
Section: Discussionmentioning
confidence: 99%
“…AMD3100 has also been reported to decrease invasion of human colorectal cancer cells in vitro [46]. Thus, blocking the interaction of CXCR4 with SDF-1 (CXCL12) may provide a novel means of preventing the invasion and metastasis of colorectal cancer.…”
Section: Page 8 Of 30mentioning
confidence: 99%
“…CXCR4 has been considered as a potential therapeutic target in several studies. A number of in vitro studies have reported that inhibiting the interactions of chemokine CXCR4 using antibodies or small molecules markedly reduces the metastasis of colorectal cancer cells (30,31); this approach could become a promising therapy for colon cancer.…”
Section: Discussionmentioning
confidence: 99%